Analisis Prediksi Data Mining Untuk Mengetahui Minat Pembeli Terhadap Produk I-Pos Pada Pt Luma Technology Indonesia Menggunakan Algoritma Klasifikasi Naive Bayes - Isarianto; Andhika Sardi, Sophian (Jurnal SIGMA, 2023)
PT Luma Technology Indonesia was established in 2007 and is engaged in software distributors for SMEs, especially products for the iPos Store Program for the Jabodetabek region. Besides being a software distributor, PT Luma Technology Indonesia also provides training services, assistance services and network installation services as after-sales services that can increase the value of the products being marketed. In addition to marketing their products offline, namely by consignment to several software stores in the Jabodetabek area, to keep up with the developments of the company, they also began using online methods to market their products such as through several e-commerce websites and social media. With so many prospective customers who submit PO on PT Luma Technology Indonesia. Then there will be a test of buying interest in prospective customers. PT Luma Technology Indonesia uses one of the classification methods, namely the naive bayesian method, to find out prospective customers who are interested or not in the ipos store program on PT Luma Technology Indonesia with a fairly high level of accuracy, in order to find out prospective customers who are interested in the ipos store program on PT Luma Technology Indonesia. Keyword: Analysis, data mining, interests, prospective customers, PT Luma Technology Indonesia, classification, naive bayes